2005
DOI: 10.1038/nn1472
|View full text |Cite
|
Sign up to set email alerts
|

ATP mediates rapid microglial response to local brain injury in vivo

Abstract: Parenchymal microglia are the principal immune cells of the brain. Time-lapse two-photon imaging of GFP-labeled microglia demonstrates that the fine termini of microglial processes are highly dynamic in the intact mouse cortex. Upon traumatic brain injury, microglial processes rapidly and autonomously converge on the site of injury without cell body movement, establishing a potential barrier between the healthy and injured tissue. This rapid chemotactic response can be mimicked by local injection of ATP and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

94
3,174
8
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 3,383 publications
(3,298 citation statements)
references
References 39 publications
94
3,174
8
22
Order By: Relevance
“…58,59 Injury-triggered extracellular ATP also affects microglial response following brain injury. 60,61 We have identified that injury-triggered lysosome exocytosis causes secretion of acid sphingomyelinase (ASM), which is needed for cell membrane repair. 16 ASM secretion by glial cells is also triggered by ATP, which in turn regulates secretion of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Injury-triggered extracellular ATP also affects microglial response following brain injury. 60,61 We have identified that injury-triggered lysosome exocytosis causes secretion of acid sphingomyelinase (ASM), which is needed for cell membrane repair. 16 ASM secretion by glial cells is also triggered by ATP, which in turn regulates secretion of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The role of microglia in brain development and function was suggested by investigation of Nasu-Hakola disease, a rare genetic dementing leukoencephalopathy caused by homozygous deficiency of triggering receptor on myeloid cells 2 (TREM2), which is only expressed in the CNS on microglia [15]. Moreover, using in vivo 2-photon imaging, the processes of cortical microglia can be shown to be constantly active, surveying the brain parenchyma every 4 h and interacting with synapses [16,17]. It is worth considering whether these active functions may later be deployed in a maladaptive fashion during neurodegenerative processes.…”
Section: The Role Of Microglia In Cns Developmentmentioning
confidence: 99%
“…Resident microglia in the healthy brain display a ''resting state" appearing in a downgraded phenotype, with highly ramified morphology and a low expression of membrane receptors that serve 0091 immunological functions [123]; even in this resting state microglia are highly active as shown by the high motility of their processes and protrusions observed by two-photon imaging analysis of brain in vivo ( [53,173]). Microglia are the first cell type that sense any form of disturbance of the brain and rapidly activate through a well-characterized and graded response; the inner cytoskeleton changes and the cell body becomes enlarged, bearing shorter and thicker cytoplasmic processes ( [174,218]).…”
Section: Role Of Microglia In Neurodegenerationmentioning
confidence: 99%